The real-world safety of Nivolumab: a pharmacovigilance analysis based on the FDA adverse event reporting system - Yutong Wu; Yue Zhou; Shiyue Xia; Zhaoyou Meng (Frontiers in Immunology)
BackgroundNivolumab, a human immunoglobulin IgG4 monoclonal antibody targeting PD-1 receptor, received initial FDA approval in 2014 for treating unresectable or metastatic malignant melanoma (MM), followed by approval for metastatic squamous and non-squamous non-small cell lung cancer (NSCLC) in 2015. With expanding clinical applications of nivolumab, comprehensive evaluation of its safety profile in real-world healthcare settings becomes increasingly crucial.MethodsWe compiled a real-world safety dataset of nivolumab from the FDA Adverse Event Reporting System (FAERS) database, encompassing reports from Q4–2014 through Q2 2024. To evaluate the association between nivolumab and adverse events (AEs), we employed four distinct disproportionality analysis methods: Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Multi-item Gamma Poisson Shrinker (MGPS) and Bayesian Confidence Propagation Neural Network (BCPNN). Additionally, we utilized Weibull distribution modeling to characterize the temporal risk patterns of identified adverse events.ResultsOur analysis identified 64,627 AEs reports associated with nivolumab. The most frequently reported AEs included fatigue, dyspnea, musculoskeletal pain, decreased appetite, cough, nausea, and constipation. Notably, we detected several potential safety signals not currently listed in the prescribing information: Malignant neoplasm progression, weight decreased, sepsis myocarditis, encephalitis and hypotension.ConclusionsOur large-scale pharmacovigilance study identified significant safety signals associated with nivolumab, including previously unrecognized adverse drug reactions. The identification of these safety signals underscores the importance of ongoing post-marketing surveillance for immune checkpoint inhibitors. Future studies should investigate the mechanisms underlying these associations and develop targeted monitoring protocols.